Potensi Layanan Perpustakaan Provinsi Papua Dalam Meningkatkan Literasi Warga Papua di Masa Pandemi Covid-19 - Nelwan Rosumbre (Ikatan Pustakawan Indonesia, 2021)
This article discusses the potential, challenges and opportunities of regional-owned library in increasing citizen literacy during the Covid-19 pandemic. In order to study this issue, literacy and public service theories are used. The main data in this study is secondary data consisting of scientific references, regulations, government documents and statistical references. Limited observations of regional library facilities are used as primary data in this study. The data analysis is conducted qualitatively with an effort to describe and explore the object under study as a whole. This study concludes that regional libraries have an important function in improving the basic literacy competences of Papuans. The Covid-19 pandemic services continue to run in accordance with standard health protocols and e-pusda services continue to run with a limited internet connection. The potential to increase citizen literacy through library functions during the pandemic is still high by integrating education, activism and library services and striving to make regional libraries as hybrid and digital libraries that allow broad access for Papuans even though the majority of them live in geographic areas isolated.